WATER CANAL SYSTEM IN PROJECTS, ACTIVITIES AND REPORTS OF POLISH AUTHORITIES IN THE 1830S-1860S - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this article is to present the endeavours undertaken in the 19th century by diverse governing bodies to build or (rebuild) and eventually improve the Polish water canal system. These activities concerned commissions from the Second Council of State, the Administrative Council, the Third Council of State and, inevitably, the Board of Land and Water Communications/Board of the 13th District of Communications, among others. In addition, some of the general state reports, especially those focusing on water transport issues, are analysed in this article. All of the researched matters deal with the following canals: Augustów, Windawa, Brudnów and Wisła-Narew.